An Effective Pre-processing Technique for Robust ESPRIT-Based Single-Tone Frequency Estimation against an I/Q Mismatch - Kim, Sangdong; Kim, Bong-seok; Oh, Daegun; Lee, Jonghun (Elektronika ir Elektrotechnika, 2015)
This letter proposes an effective pre-processing technique for robust estimation of signal parameters via rotational invariance techniques (ESPRIT)-based single-tone frequency estimation against an I/Q mismatch. For the implementation of a high-accuracy ranging/radar system, parametric-based algorithms such as MUSIC, ESPRIT and their variations have been adopted due to their superior estimation capability for single-tone frequency estimations. Since most ranging/radar system have the direct conversion architecture, I/Q imbalance problem occurs in the form of spurious frequencies of the frequency spectrum. For this reason, the proposed pre-processing technique is designed to make use of the Hilbert transform structure for received signals. The estimation performance of the proposed pre-processing technique in single-tone frequency is derived and compared with the results from a Monte-Carlo simulation. The root-mean-square error (RMSE) of the proposed method is compared with that of an ESPRIT-based method for various parameters. DOI: http://dx.doi.org/10.5755/j01.eee.21.6.13757